161k views
4 votes
If f(x)= 5 ^ x + 2x and g(x)= 3x - 6, find (f+g)(x)​

User Brian Buck
by
4.8k points

2 Answers

5 votes

Answer:


5^x+5x-6

Explanation:


f(x)=5^x + 2x


g(x)= 3x - 6


(f+g)(x)


f(x) + g(x)


5^x+2x+3x-6


5^x+5x-6

User James Goodwin
by
4.9k points
2 votes

Answer:

(f+g)(x)​ is 5^x + 5x - 6

Explanation:

To find (f + g)(x), we are merely adding up all the terms present in both

f(x)= 5^x + 2x and g(x)= 3x - 6. 5^x is unique and cannot be combined with any other term. 2x and 3x can be combined to obtain 5x. -6 is unique.

Thus, the sum (f+g)(x)​ is 5^x + 5x - 6.

User Naveed
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.